Study on the length of speed change lanes at the entrance and exit of two-way ten-lane expressways - Chen, Ling; Xiong, Dan; Yu, Quan; Guo, Huihui (Frontiers in Built Environment, 2025)
As the economy continues to develop rapidly, traffic volume on highways has increased dramatically, leading to increasingly severe congestion issues. In response, expanding expressways to two-way ten-lane configurations has become a mainstream strategy to alleviate traffic pressure. Given the absence of unified national standards for the design of two-way ten-lane highways, this study explores the relationship between the form and design parameters of speed change lanes. Using VISSIM simulation and the Surrogate Safety Assessment Model, we investigate the impact of different speed change lane lengths on traffic efficiency and safety under various traffic flow conditions on renovated and expanded two-way ten-lane highways. Key performance indicators include average delay time, average queue length, number of conflicts, and Post-Encroachment Time. The results show that, at a mainline design speed of 120 km/h, a 270-m acceleration lane reduces conflicts by 47.6% compared to conventional lengths, while a 161-m deceleration lane achieves a 32.8% reduction. This study provides crucial insights for the rational design of speed change lane lengths on two-way ten-lane highways, ultimately enhancing road capacity, improving safety, and optimizing traffic resource allocation.